“Plan de Marketing para el Hotel Villonaco en la Ciudad de Loja, provincia de Loja” - Chuquimarca Jaramillo, Mireya Elizabeth (2024)
The purpose of this research work called “Marketing Plan for the Villonaco Hotel in the City of Loja, province of Loja” is to contribute to the growth of the company. Currently, marketing today is a key tool that focuses on investigating the needs of users and how they can be met, which is why the development of this work is considered necessary, the objective of which is to diagnose the current situation of the company. and establish marketing strategies that allow the company to achieve greater positioning within the hotel market in the City of Loja. In the methodology used, tools such as observation, surveys directed at users, interviews aimed at the administrative area were used, which provided useful information for the preparation of matrices and to be able to make a situational diagnosis of the company, such as the EFI matrix that describes both internal weaknesses and strengths of the business, while for the external study an EFE matrix was used indicating opportunities and threats. Subsequently, to achieve strategies, the SWOT matrix was developed, in which we identified strengths, weaknesses, and threats in order to develop a strategic plan, together with the application of a combined matrix, obtaining as an effect four objectives focused on promotion, service improvement and implement an action plan on social networks to increase brand visibility. Finally, conclusions and recommendations are issued based on the results obtained that will support the Hotel Villonaco to achieve its stated objectives.